1977
DOI: 10.2307/1128477
|View full text |Cite
|
Sign up to set email alerts
|

Infant Crying and Maternal Responsiveness: A Rejoinder to Gewirtz and Boyd

Abstract: The criticisms leveled by Gewirtz and Boyd focus on 1 of 6 analyses upon which Bell and Ainsworth based their interpretation of findings--namely, cross-quarter correlations of measures of infant crying and maternal response. It is maintained that these measures were approximate, and that they were independent of each other in cross-quarter correlations. It is also maintained that the statistical procedures were appropriate to a small sample of subjects in naturalistic, longitudinal research. The three "illustr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

1978
1978
2014
2014

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(11 citation statements)
references
References 7 publications
(13 reference statements)
0
11
0
Order By: Relevance
“…An important tenet of attachment theory is that parents who are sensitive and responsive to their children are more likely to have children who are securely attached to their parents. Researchers consider children's secure attachment to the caregiver to be a hallmark of socio emotional growth and development in the infancy and toddler period (Ainsworth, 1973). Attachment theory also suggests that the thoughts and feelings that fathers (and mothers) have toward their children are linked to the quality of parenting (Ainsworth, 1973).…”
Section: Risk and Resilience Perspective Identity Theory Attachmentmentioning
confidence: 99%
See 2 more Smart Citations
“…An important tenet of attachment theory is that parents who are sensitive and responsive to their children are more likely to have children who are securely attached to their parents. Researchers consider children's secure attachment to the caregiver to be a hallmark of socio emotional growth and development in the infancy and toddler period (Ainsworth, 1973). Attachment theory also suggests that the thoughts and feelings that fathers (and mothers) have toward their children are linked to the quality of parenting (Ainsworth, 1973).…”
Section: Risk and Resilience Perspective Identity Theory Attachmentmentioning
confidence: 99%
“…Researchers consider children's secure attachment to the caregiver to be a hallmark of socio emotional growth and development in the infancy and toddler period (Ainsworth, 1973). Attachment theory also suggests that the thoughts and feelings that fathers (and mothers) have toward their children are linked to the quality of parenting (Ainsworth, 1973). Fathers who have positive feelings about their child are likely to be more responsive and sensitive to their infants than fathers who do not have positive feeling toward the child.…”
Section: Risk and Resilience Perspective Identity Theory Attachmentmentioning
confidence: 99%
See 1 more Smart Citation
“…In laboratory experimentation it has been found that ignoring a cry leads to decreased crying (Etzel & Gewirtz, 1967), while at home, over a longer period of time, ignoring a cry is associated with more frequent crying . Such inconsistencies can lead to acrimonious argument (Ainsworth & Bell, 1977;Gewirtz & Boyd, 1977a, 1977c or sterile cross-paradigmatic controversy (Kuhn, 1962). Such inconsistencies can lead to acrimonious argument (Ainsworth & Bell, 1977;Gewirtz & Boyd, 1977a, 1977c or sterile cross-paradigmatic controversy (Kuhn, 1962).…”
Section: Strategies For Researchmentioning
confidence: 99%
“…(In fact, different results have been obtained in the home and in the laboratory; for example, the effect of responding immediately and contingently to an infant cry seems to be to increase subsequent crying in laboratory studies and to decrease crying in home studies [Ainsworth & Bell, 1977;Gewirtz & Boyd, 1977a, 1977b.) Most of these laboratory experiments used an adult experimenter as a parent substitute.…”
mentioning
confidence: 99%